Decomposition of Differences in PISA Results in Middle Income Countries - Sandra Nieto; Raul Ramos (Institute for the Study of Labor (IZA), 2014)
Our objective is to analyse the role of teacher and school quality to explain differences in students' educational outcomes. With this aim, we use PISA microdata for 10 middle income and 2 high income countries and we apply decomposition methods in order to identify the role of these factors for different groups of students. Our results show that school and teacher quality and better practices matter even in different institutional settings. From a policy perspective, this evidence supports actions addressed at improving both factors in order to reduce cross-country differences but also between students at the top and bottom distribution in terms of socio-economic characteristics.
Keywords: J24; I21; I25; 330; educational outcomes; teacher and school quality; PISA; decomposition methods; middle-income countries